Wolbachia-infected mosquito to suppress the transmission chain of mosquito- borne virus: A systematic review and meta—analysis of community-based health intervention trials - Muhammad Afif Naufal; Hafsa Hapsari; Talitha Dinda Gunawan; Robert Sinto (Asian Pacific Journal of Tropical Medicine)
Objective: To identify the efficacy of Wolbachia-based intervention by reviewing community-based trials through meta-analysis and systematic review methods. Methods: Studies about Wolbachia-infected mosquito intervention were collected through a screening process. Records underwent data extraction and quality assessment independently by the authors. The primary outcome of the study was protective efficacy. Quantitative analysis was conducted through meta-analysis and multivariate meta-regression using Rstudio Ver.2024.09.0-375. Qualitative analysis was done by summarizing records’ findings. Results: 10 out of the 10 660 records met the criteria. The evidence was moderate in quality and highly heterogeneous. Intervention consisted of releasing Wolbachia-infected Aedes aegypti in densely populated settlements. The combined protective efficacy of Wolbachia intervention against dengue is highly heterogeneous (79%; 95% CI 70-88; I2=98%). wMel strain is significantly more efficacious compared to wAlbB (protective efficacy 84%; 95% CI 76-93; I2=95%) vs. 64% (95% CI 46-82; I2=85%); P<0.01) in preventing dengue cases. Wolbachia-infected mosquito populations were found to be unstable upon release cessation, which necessitated periodic release and monitoring to maintain desired concentration and protective efficacy. Conclusions: Wolbachia-based intervention is effective in suppressing the transmission of mosquito-borne diseases, especially dengue, with an excellent safety profile. However, community acceptance and policy remain as significant barriers to implementation.